2022
DOI: 10.1091/mbc.e21-09-0443
|View full text |Cite|
|
Sign up to set email alerts
|

The ARF GAPs ELMOD1 and ELMOD3 act at the Golgi and cilia to regulate ciliogenesis and ciliary protein traffic

Abstract: ELMODs are a family of three mammalian paralogs that display GTPase activating protein (GAP) activity towards a uniquely broad array of ADP-ribosylation factor (ARF) family GTPases that includes ARF-like (ARL) proteins. ELMODs are ubiquitously expressed in mammalian tissues, highly conserved across eukaryotes, and ancient in origin, being present in the last eukaryotic common ancestor. We described functions of ELMOD2 in immortalized mouse embryonic fibroblasts (MEFs) in the regulation of cell division, microt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 102 publications
(279 reference statements)
2
15
0
Order By: Relevance
“…Our findings of INPP5E and IFT140 accumulation at the Golgi in Arl16 KOs and INPP5E but not IFT140 at the Golgi in Pde6d KOs support our model of ARL16 regulating two novel, independent traffic pathways from the Golgi to cilia. Finally, in a parallel study carried out in our lab we found phenotypes very similar to those reported here in Arl16 KO lines when MEFs were deleted for either of the ARF/ARL GAPs ELMOD1 or ELMOD3 ( Turn et al. , 2022 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our findings of INPP5E and IFT140 accumulation at the Golgi in Arl16 KOs and INPP5E but not IFT140 at the Golgi in Pde6d KOs support our model of ARL16 regulating two novel, independent traffic pathways from the Golgi to cilia. Finally, in a parallel study carried out in our lab we found phenotypes very similar to those reported here in Arl16 KO lines when MEFs were deleted for either of the ARF/ARL GAPs ELMOD1 or ELMOD3 ( Turn et al. , 2022 ).…”
Section: Discussionsupporting
confidence: 85%
“…, 2022 ). In addition, expression of ARL16-myc in Elmod1 or Elmod3 KO cells was able to reverse those phenotypes ( Turn et al. , 2022 ), providing strong support for a model that includes these two proteins as acting in concert with ARL16 at the Golgi and in ciliary biology.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In contrast, ELMOD family members are thought to act as ARF/ARL GAPs, with broad cellular effects, including on the actin cytoskeleton (Li et al, 2019b). All three vertebrate ELMOD proteins have recently been localized to basal bodies and linked to ciliogenesis, albeit with seemingly opposing effects: While loss of ELMOD1 and 3 reduced ciliation in mouse embryonic fibroblasts, loss of ELMOD2 actually resulted in an increase, with those cilia displaying abnormal morphology, including apparent splaying of axonemes and ciliary rootlet defects (Turn et al, 2022; Turn et al, 2021) (ultrastructural analysis has so far not been performed). Common to all three perturbations is a mislocalization of ciliary proteins, suggesting ciliary trafficking is at least partly responsible for the observed defects (Turn et al ., 2022; Turn et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%